Lo-Fi aesthetics in popular music discourse - Harper, A; Adam Harper (2014)
During the late twentieth and early twenty-first centuries, 'lo-fi,' a term suggesting poor sound quality, the opposite of 'hi-fi,' became a characteristic perceived in certain popular-music recordings and eventually emerged as a category within independent or 'indie' popular music. It is typically taken to express the technical and technological deficiencies associated with amateur or 'DIY' musical production, namely at home using cheap recording equipment. However, this thesis rejects the assumption that lo-fi equates to a mode of production and charts it as a construction and a certain aesthetics within popular music discourse, defined as 'a positive appreciation of what are perceived and/or considered normatively interpreted as imperfections in a recording.' I chart the development and manifestation of lo-fi aesthetics, and the ways it focuses on various 'lo-fi effects' such as noise, distortion ('phonographic imperfections') and performance imperfections, in several decades of newspapers, magazines and websites covering popular music in the English-speaking world. I argue that lo-fi aesthetics is not merely the unmediated, realist authenticity that it is often claimed to be, but one that is also fascinated with the distance from perceived commercial norms of technique and technology (or 'technocracy') that lo-fi effects signify. Lo-fi aesthetics derives from aesthetics of primitivism and realism that extend back long before phonographic imperfections were positively received. I also differentiate between lo-fi aesthetics and aesthetics of noise music, distortion in rock, glitch, punk and cassette culture. An appreciation for recording imperfections and the development of 'lo-fi' as a construction and a category is charted since the 1950s and particularly in the 1980s, 1990s and in the twenty-first century, taking in the reception of artists such as the Velvet Underground, Bob Dylan, Hasil Adkins, the Shaggs, Jandek, Daniel Johnston, Beat Happening, Pavement, Sebadoh, Guided By Voices, Beck, Will Oldham, Ariel Pink and Willis Earl Beal.